Proliferative enteropathy caused by Lawsonia intracellularis in rabbits in Southern Brazil - Cecco, Bianca Santana de; Kemper, Regina Tose; Sousa, Susy Hermes de; Leite-Filho, Ronaldo Viana; Cruz, Raquel Aparecida Sales da; Guedes, Roberto Mauricio Carvalho; Driemeier, David; Sonne, Luciana (Semina: Ciências Agrárias, 2020)
Proliferative enteropathy (PE), also known as ileitis, is a disease caused by the bacterium Lawsonia intracellularis. This disease is characterized by diarrhea and ill-thrift. The aim of this study is to describe a PE outbreak in rabbits that occurred in Southern Brazil. The farm had 700 rabbits at the time the outbreak occurred. The clinical signs were severe diarrhea, dehydration, and apathy. Necropsy was performed in 33 rabbits, and the most evident macroscopic findings were thickening of the intestinal wall, intestinal loops distended by large amounts of gas, and liquid feces. Histopathological examination demonstrated a marked proliferation of enterocytes in intestinal crypts, decrease number of goblet cells, and crypts microabscesses. Silver impregnation technique (Warthin-Starry) demonstrated in intestinal crypts inside of enterocytes cytoplasm, curved vibrioid bacteria compatible with L. intracellularis. Immunohistochemical staining with anti-L. intracellularis confirmed the agent presence. PCR was performed and L. intracellularis was confirmed as the etiological agent.